Osteochondral Allograft of the Talus - Bisicchia, Salvatore (The University of Iowa, 2014)
Osteochondral lesions of the talus are being recognized as an increasingly common injury. They are most commonly located postero-medially or antero-laterally, while centrally located lesions are uncommon. Large osteochondral lesions have significant biomechanical consequences and often require resurfacing with osteochondral autograft transfer, mosaicplasty, autologous chondrocyte implantation (or similar methods) or osteochondral allograft transplantation. Allograft procedures have become popular due to inherent advantages over other resurfacing techniques. Cartilage viability is one of the most important factors for successful clinical outcomes after transplantation of osteochondral allografts and is related to storage length and intra-operative factors. While there is abundant literature about osteochondral allograft transplantation in the knee, there are few papers about this procedure in the talus. Failure of non-operative management, initial debridement, curettage or microfractures are an indication for resurfacing. Patients should have a functional ankle motion, closed growth plates, absence of cartilage lesions on the tibial side. This paper reviews the published literature about osteochondral allograft transplantation of the talus focusing on indications, pre-operative planning, surgical approaches, postoperative management, results and complications of this procedure.